The effect of self-esteem on the development of frustration tolerance in adolescence - Bozhok, Natalia (My University, 2013)
In the article, the phenomenon of «frustration tolerance» in adolescence is considered. The peculiarities of self-esteem in students’ age are determined. The impact of self-esteem on the high frustration tolerance formation in adolescence is analyzed.
Keywords: adolescence; self-esteem; high frustration tolerance; самооценка; фрустрационная толерантность; юность; самооцінка; фрустраційна толерантність; юність; кафедра ділової іноземної мови та міжнародної комунікації